Age at Preschool Entrance and Noncognitive Skills before School - An Instrumental Variable Approach - Martin Schlotter (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
We estimate the effect of age at preschool entrance on crucial noncognitive skills in theyear before school starts. Using an instrumental variable approach and exploiting cut-offdates for the time at preschool entrance we find that children entering preschool earlierin life have better noncognitive skills in terms of being more assertive and being moreable to form friendships. Hence, our results offer general empirical evidence for thenon-linearity in the skill formation process. Moreover they show that entering preschoolat an early age is an important prerequisite for the development of social schoolreadiness.
Keywords: I20; J13; J24; 330; Preschool; noncognitive skills; instrumental variables; entrance effects; Kinder; Altersgruppe; Kognition; Kinderbetreuungseinrichtung; Schätzung; Deutschland